Large‐scale degradation of Amazonian freshwater ecosystems - Leandro Castello; Marcia N. Macedo (Global Change Biology, 2016)
Hydrological connectivity regulates the structure and function of Amazonian freshwater ecosystems and the provisioning of services that sustain local populations. This connectivity is increasingly being disrupted by the construction of dams, mining, land‐cover changes, and global climate change. This review analyzes these drivers of degradation, evaluates their impacts on hydrological connectivity, and identifies policy deficiencies that hinder freshwater ecosystem protection. There are 154 large hydroelectric dams in operation today, and 21 dams under construction. The current trajectory of dam construction will leave only three free‐flowing tributaries in the next few decades if all 277 planned dams are completed. Land‐cover changes driven by mining, dam and road construction, agriculture and cattle ranching have already affected ~20% of the Basin and up to ~50% of riparian forests in some regions. Global climate change will likely exacerbate these impacts by creating warmer and dryer conditions, with less predictable rainfall and more extreme events (e.g., droughts and floods). The resulting hydrological alterations are rapidly degrading freshwater ecosystems, both independently and via complex feedbacks and synergistic interactions. The ecosystem impacts include biodiversity loss, warmer stream temperatures, stronger and more frequent floodplain fires, and changes to biogeochemical cycles, transport of organic and inorganic materials, and freshwater community structure and function. The impacts also include reductions in water quality, fish yields, and availability of water for navigation, power generation, and human use. This degradation of Amazonian freshwater ecosystems cannot be curbed presently because existing policies are inconsistent across the Basin, ignore cumulative effects, and overlook the hydrological connectivity of freshwater ecosystems. Maintaining the integrity of these freshwater ecosystems requires a basinwide research and policy framework to understand and manage hydrological connectivity across multiple spatial scales and jurisdictional boundaries.